Porphyran from discolored nori prevents metabolic syndrome through microbiota-bile acid-ceramide pathway - Yoko Yokoyama; Yoko Takashina; Jean-David Morel; Tanon Taworntawat; Naho Kitamura; Utana Nagano; Tatsuya Tanigaki; Anna Nakamura; Teruo Miyazaki; Hiroki Taoka; Adrienne Mottis; Alessia Perino; et al. (iScience)
Summary: Nori is a component of the traditional Japanese diet. The Japanese have a low prevalence of obesity and cardiovascular disease worldwide, and components of nori may have disease-preventive effects. Here, we focused on porphyran, which is abundant in nori that is discarded due to discoloration, and investigated the effects of nori-derived porphyran on gut microbiota, bile acid composition, and ceramide synthesis. Administration of porphyran to mice prevented obesity, diabetes, metabolic dysfunction-associated steatohepatitis (MASH), and hepatocellular carcinoma (HCC). This improvement correlates with a decrease in secondary bile acids, a decrease in intestinal farnesoid X receptor (FXR) signaling, and a marked decrease in blood ceramide. Porphyran, abundant in discolored nori, should be the subject of future translational research to prevent diseases with significant unmet medical needs and improve global environmental sustainability.